Mengukur Pertumbuhan PDRB Hijau Atas Dasar Harga Berlaku (ADHB) Sub Sektor Tanaman Perkebunan di Kalimantan: Studi Kasus Tahun 2010, 2015, dan 202 - Nugroho, Niti (PPJP ULM, 2023)
This study aims to determine the magnitude of the value of depletion and plantation degradation and the growth rate of Green GRDP in the current price of the Plantation Crops Sub-Sector in Kalimantan Region 2010, 2015, and 2020. The secondary data is collected from Badan Pusat Statistik. The analysis technique is used in the Green GRDP calculation method. The results show the regional depletion value of Kalimantan was Rp 14.56 trillion in 2010, Rp 28.72 trillion in 2015, and Rp 53.37 trillion in 2020. The value of regional degradation in Kalimantan in 2010 was Rp 1.57 billion, then Rp 35.52 billion in 2015, and Rp 4.78 billion in 2020. The growth rate of Green GRDP in current price tends to weaken where the growth rate in 2010-2015 was 55.52% and in 2015-2020 dropped to 12.23%.